COMPARISON OF THE PRAGMATIC FEATURES OF PHRASES IN THE RUSSIAN AND UZBEK LANGUAGES ON THE EXAMPLE OF WORKS OF ART (Web of Teachers: Inderscience Research, 2024)
This article presents a comparative analysis of the pragmatic features of phrases in Russian and Uzbek languages, emphasizing how these features are represented in works of art. Through analyzing language structures, cultural contexts, and idiomatic expressions in selected literary works, we reveal how pragmatics function differently across these two languages. The study highlights the impact of sociocultural context on language usage and the challenges of translating idiomatic expressions and cultural references. Our findings suggest that the pragmatic characteristics of Russian and Uzbek are deeply rooted in historical and cultural backgrounds, influencing both language structure and meaning interpretation.